Distribusi Ketenagakerjaan dan Tingkat Kesejahteraan Petani di Pedesaan Agroekosistem Lahan Kering Berbasis Komoditas Palawija - Sugiarto, Sugiarto (Politeknik Negeri Lampung., 2011)
The purpose of this research is to know the aspect labor absorption and prosperity level in dry agroecosystem. This research was taken in PATANAS (Panel Petani National) villages including dry agroecosystem 2008. The data was analyzed by simple statistic and showed using cross tabulation analysis. The result is show that labor absorption in villages is still dominated by agriculture sector, which is changing from under elementary school. Beside that, labor force absorption for younger age is increasing which is showed by movement of the amount of labor from agriculture sector to non agriculture sector. In other hand, the development of prosperity level in the villages is varieties, among in 3 villages no prosperity and 5 villages is prosperity. It means that the availability of labor force which absorption different means of livelihood and the revenue in agro ecosystem wet land didn?t show any development than agro ecosystem dry land villages. So that policy to increase farmers property is needed through variety aspect to support revenue development in agriculture and non agriculture sectors, and agriculture commodity price policy which suitable for farmers and also push work climate out of agriculture Keywords : labor structure, prosperity level household